Coastal Inundation Model in the Coastal Area of Palopo City, South Sulawesi Province - Riza Aitiando Pasaribu; Pandu Setya Budi; Muhamad Abdul Ghofur Al Hakim; Farel Ahadyatulakbar Aditama; Nurina Hanum Ayuningtyas (Journal of Applied Geospatial Information, 2021)
The impact of sea-level rise is perceived by many archipelagic countries such as Indonesia. The higher the sea level rises every year, the larger the disaster threat in the coastal area. The current condition of most coastal areas indicates various pressures caused by city development, including the coastal area of Palopo City in South Sulawesi Province. The sea-level rise is suspected to be the cause of coastal inundation in Palopo City which, so far has not been identified. Therefore, this study aims to draw a coastal vulnerability map of sub-districts in Palopo caused by coastal inundation using GIS technology. Analysis of the areas affected by coastal inundation is carried out by processing spatial data. The sub-districts areas affected by coastal inundation are only those located in the coastal zones. The affected area in Bara, Wara Selatan, Wara Utara, Wara Timur, and Telluwana sub-districts are 160.64 ha, 21.41 ha, 73.55 ha, 87.56 ha, and 56.65 ha, respectively. In Bara Sub-district, the areas affected by coastal inundation are residential and mangrove conservation areas. The affected areas in Telluwana Sub-district are residential, production forest, coastal conservation, and mangrove conservation areas. The affected areas in Wara Selatan, Wara Timur, and Wara Utara Sub-districts are all residential areas. By using sea-level rise data of 27 years with its highest tide model, the coastal inundation in 2040 which is predicted to occur in Palopo City can be modeled properly.